Bayesian Color Constancy with Non-Gaussian Models - Rosenberg, Charles; Minka, Tom; Ladsariya, Alok (NIPS2003, 2003)
Plots of slices of the three dimensional (32x32x32) color surface reflectance distribution along a single dimension: •Row one plots green versus blue and slices in red whose magnitude increases from left to right. •Row two plots red versus blue with slices in green whose magnitude increases from left to right. •Row three plots red versus green with slices in blue whose magnitude increases from left to right. Plots are scaled by a factor of 2 in each dimension to make the structure more visible.